Quantifying the Total and Bioavailable Polycyclic Aromatic Hydrocarbons and Dioxins in Biochars - Hale, Sarah E; Lehmann, Johannes; Rutherford, David; Zimmerman, Andrew R; Bachmann, Robert T; Shitumbanuma, Victor; O’Toole, Adam; Sundqvist, Kristina L; Arp, Hans Peter H; Cornelissen, Gerard (Environmental science & technology, 2012)
Biochar soil amendment is advocated to mitigate climate change and improve soil fertility. A concern though, is that during biochar preparation PAHs and dioxins are likely formed. These contaminants can possibly be present in the biochar matrix and even bioavailable to exposed organisms. Here we quantify total and bioavailable PAHs and dioxins in a suite of over 50 biochars produced via slow pyrolysis between 250 and 900 °C, using various methods and biomass from tropical, boreal, and temperate areas. These slow pyrolysis biochars, which can be produced locally on farms with minimum resources, are also compared to biochar produced using the industrial methods of fast pyrolysis and gasification. Total concentrations were measured with a Soxhlet extraction and bioavailable concentrations were measured with polyoxymethylene passive samplers. Total PAH concentrations ranged from 0.07 μg g–1 to 3.27 μg g–1 for the slow pyrolysis biochars and were dependent on biomass source, pyrolysis temperature, and time. With increasing pyrolysis time and temperature, PAH concentrations generally decreased. These total concentrations were below existing environmental quality standards for concentrations of PAHs in soils. Total PAH concentrations in the fast pyrolysis and gasification biochar were 0.3 μg g–1 and 45 μg g–1, respectively, with maximum levels exceeding some quality standards. Concentrations of bioavailable PAHs in slow pyrolysis biochars ranged from 0.17 ng L–1 to 10.0 ng L–1which is lower than concentrations reported for relatively clean urban sediments. The gasification produced biochar sample had the highest bioavailable concentration (162 ± 71 ng L–1). Total dioxin concentrations were low (up to 92 pg g–1) and bioavailable concentrations were below the analytical limit of detection. No clear pattern of how strongly PAHs were bound to different biochars was found based on the biochars’ physicochemical properties.